Zosteriform Lichen Planus: case report of a rare variant of Lichen Planus - Kanthilatha Pai; Sathish Pai (Our Dermatology Online, 2013)
Since its original description by Devergie in 1854, several cases of linear lichen planus have been described in the literature, but there have been notably few cases of the more rare zosteriform lichen planus. Zosteriform lichen planus needs to be differentiated from linear lichen planus and other linear dermatoses. We present a case of Zosteriform Lichen planus for its rarity and briefly review literature.